A hydrolyzed polyacrylonitrile-based nanofiltration membrane and its preparation method and application

By using a combination of hydrolyzed polyacrylonitrile, graphene oxide and polyelectrolyte, the nanofiltration membrane was prepared by using a non-solvent-induced phase conversion method, which solved the trade-off problem between the existing nanofiltration membranes in improving water flux and retention, and achieved efficient and environmentally friendly nanofiltration membrane preparation, with high water flux and high retention.

CN119056252BActive Publication Date: 2025-03-14LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411209962.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-03-14
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Existing nanofiltration membranes often sacrifice interception while increasing water flux, and vice versa, resulting in limited improvement in membrane performance, especially when dealing with complex water quality and high concentration of pollutants, it is difficult to take into account high water flux and high solute interception.

Method used

Hydrolyzed polyacrylonitrile (H-PAN) is used as the base membrane material, combined with graphene oxide and polyelectrolyte that can complex with the base membrane material, and an integrated membrane structure is prepared by a non-solvent-induced phase conversion method including chemical reactions to achieve efficient preparation of nanofiltration membranes.

Benefits of technology

The trade-off effect between water flux and retention rate was successfully broken, and the dual advantages of high water flux and high retention rate of nanofiltration membrane were realized, while reducing the use of organic solvents, improving the environmental protection and cost-effectiveness of the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119056252B_ABST
    Figure CN119056252B_ABST
Patent Text Reader

Abstract

The present invention proposes a hydrolyzed polyacrylonitrile-based nanofiltration membrane and a preparation method and application thereof, which belongs to the technical field of nanofiltration membranes and is used to solve the technical problem that the water flux and solute retention rate of the nanofiltration membrane are difficult to take into account and the stability is poor. The preparation method of the nanofiltration membrane of the present invention comprises the following steps: first, the hydrolyzed polyacrylonitrile is dissolved in a solvent as a base membrane material to prepare a casting solution; then the polyelectrolyte that can react with the base membrane material is dissolved in deionized water to obtain a uniform and transparent solution, which is used as a coagulation bath for membrane preparation. Finally, graphene oxide is added to the casting solution or the coagulation bath according to a certain ratio as an auxiliary membrane separation cortex construction material, and the nanofiltration membrane is prepared by a chemical reaction coupling non-solvent induced phase inversion method. The membrane preparation method can simultaneously improve the water flux and dye retention rate of the nanofiltration membrane, and the separation performance of the obtained nanofiltration membrane breaks the trade-off effect between the flux and the retention rate of the membrane. The nanofiltration membrane is suitable for purifying surface water, treating printing and dyeing industrial wastewater and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanofiltration membranes, and in particular relates to a hydrolyzed polyacrylonitrile-based nanofiltration membrane and a preparation method and application thereof. Background Art

[0002] As the global water shortage and water pollution become increasingly serious, the research and development of water treatment technology has become particularly important. As a highly efficient means of water purification, nanofiltration membrane technology has become one of the key technologies in the field of water treatment because it can remove harmful substances in water such as heavy metal ions, organic pollutants and some salts while retaining minerals in water.

[0003] Nanofiltration membrane separation technology is widely used in the fields of surface water purification, industrial wastewater treatment and seawater desalination due to its high efficiency, low energy consumption, no phase change and environmental friendliness. As the core of membrane separation technology, the main feature of nanofiltration membrane is that it can intercept organic molecules or multivalent inorganic salt ions with a relative molecular mass greater than 300 at a relatively low operating pressure, while selectively passing monovalent ions. At present, the preparation methods of nanofiltration membranes include interfacial polymerization, self-assembly and phase inversion. However, there is a trade-off effect between the water flux and the retention rate of the nanofiltration membrane prepared by the above conventional membrane preparation methods. The existence of this effect limits the further improvement of the performance of the nanofiltration membrane, especially when treating complex water quality and high-concentration pollutants. Therefore, it is difficult to prepare a nanofiltration membrane with both high water flux and solute retention rate.

[0004] In the document Water Research, 194 (2021) 116825, it is mentioned that the traditional nanofiltration membrane preparation method often sacrifices the interception rate while increasing the water flux, and vice versa, which limits the efficiency of the membrane in practical applications. In the document Journal of Cleaner Production, 279 (2020) 123351, the potential impact of the traditional phase inversion method on the environment during membrane preparation is discussed, including the use of organic solvents and the difficulty of recycling. In the document Journal of Membrane Science, 580 (2019) 55-64, it is pointed out that many existing nanofiltration membranes will encounter problems of structural degradation and performance degradation in long-term operation. In the document Separation and Purification Technology, 266 (2021) 118445, the limitations of specific nanofiltration membranes in treating specific types of pollutants are discussed, which limits their application in a wider range of fields. At present, the research on nanofiltration membranes mainly focuses on the development of new membrane materials, the improvement of membrane preparation technology, the optimization of membrane performance, the assessment of environmental impacts and the expansion of application fields. Summary of the invention

[0005] In view of the technical problems that it is difficult to balance the water flux and solute retention rate of nanofiltration membranes and their poor stability, the present invention proposes a hydrolyzed polyacrylonitrile-based nanofiltration membrane and a preparation method and application thereof. The prepared nanofiltration membrane can overcome the trade-off effect between the flux and the retention rate of the membrane, achieve efficient improvement of the membrane performance, thereby having both high water flux and solute retention rate, and meet the challenges of current and future water treatment technologies.

[0006] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0007] A hydrolyzed polyacrylonitrile-based nanofiltration membrane, the preparation method of which is as follows:

[0008] The casting solution is prepared by using hydrolyzed polyacrylonitrile as the base membrane material;

[0009] A mixed solution of graphene oxide and a polyelectrolyte capable of undergoing a complex reaction with a base film material is used as a coagulation bath;

[0010] The integrated membrane structure is prepared by a one-step non-solvent induced phase inversion method including a chemical reaction, wherein the separation cortex of the nanofiltration membrane is prepared by a complex reaction of base membrane material, graphene oxide and polyelectrolyte, and then chemically cross-linked.

[0011] For the preparation of nanofiltration membrane, hydrolyzed polyacrylonitrile (H-PAN) was first selected as the base membrane material, and alkaline polyelectrolyte polyethyleneimine (PEI) which can react with the base membrane material was used as the auxiliary membrane skin construction material, which was dissolved in deionized water as a coagulation bath, and the nanofiltration membrane was prepared by a non-solvent induced phase inversion method including a one-step complexation. More specifically:

[0012] The base membrane material, hydrolyzed polyacrylonitrile (H-PAN), is fully dissolved in a solvent, and GO is ultrasonically dispersed in the solvent; the two are then mixed in a certain proportion to obtain an H-PAN / GO mixed solution; the mixed solution is fully mixed by stirring to obtain a transparent and uniform polymer solution; the polymer solution is then centrifuged at high speed to remove impurities and bubbles, thereby obtaining a polymer casting solution containing GO.

[0013] After obtaining the polymer solution, in order to avoid the influence of impurities and gases in the polymer solution on the nanofiltration membrane, the polymer solution is poured onto the surface of the support after high-speed centrifugation, and the film is scraped to ensure the uniformity of the nanofiltration membrane. The film scraping can be carried out according to the technical means well known to those skilled in the art, and there is no special limitation in this application; for example, the film is scraped by a scraper in this application, and the blade gap of the scraper is 150μm. The preferred scraping environment temperature of this application is room temperature 30±5℃, and the coagulation bath temperature is 30±2℃; after scraping, the primary film is obtained, and the primary film is immediately immersed in the coagulation bath solution for phase inversion to obtain a nanofiltration membrane. The placement time in the above coagulation bath solution is 20 to 30min. The coagulation bath is a PEI solution with a concentration of 0.1wt% to 1.0wt%, a polyallylamine solution or a soluble mixed solution of a PEI solution and a graphene oxide dispersion, wherein the graphene oxide concentration is 0.005wt%. In order to crosslink the nanofiltration membrane with glutaraldehyde, the present application preferably takes the membrane out of the coagulation bath and puts it into a 60°C, 0.5% glutaraldehyde aqueous solution for 30 minutes for crosslinking reaction. After the crosslinking reaction is completed, the crosslinked nanofiltration membrane is taken out from the glutaraldehyde aqueous solution and soaked in deionized water, and stored in deionized water for use.

[0014] The flow chart of preparing nanofiltration membrane in this application is as follows Figure 1 As shown, the preparation process of the nanofiltration membrane specifically includes: polymer solution (preparation of casting solution) - scraping the membrane on the support - phase inversion in the coagulation bath - crosslinking in the glutaraldehyde solution - immersion of the membrane in water - finished membrane. The support described in this application is a support well known to those skilled in the art, but for the nanofiltration membrane, the embodiment of this application preferably uses polyester non-woven fabric.

[0015] Beneficial effects of the present invention:

[0016] (1) The present invention provides a method for preparing a nanofiltration membrane. The nanofiltration membrane is characterized in that hydrolyzed polyacrylonitrile is used as a base membrane material, graphene oxide and a polyelectrolyte that can undergo a complex reaction with the base membrane material are used as auxiliary membrane separation cortical construction materials, and a complex reaction is introduced into the process of membrane preparation by a non-solvent induced phase inversion method to prepare an asymmetric nanofiltration membrane with an integrated structure through a non-solvent induced phase inversion method that includes a complex reaction in one step.

[0017] (2) The present invention effectively regulates the phase separation process of the primary membrane and accelerates the phase conversion rate by introducing the complex reaction between the base membrane material and graphene oxide and / or polyelectrolyte; at the same time, the graphene oxide and polyelectrolyte are immobilized on the membrane surface, which is conducive to the formation of a dense and ultra-thin membrane separation cortex. Therefore, the nanofiltration membrane prepared by this method successfully breaks the trade-off effect between the flux and the retention rate of the membrane, and achieves the dual advantages of high water flux and high retention rate. In addition, the non-solvent induced phase conversion method used reduces the use of organic solvents, improves the environmental friendliness of the preparation process, and reduces costs.

[0018] (3) The hydrolyzed polyacrylonitrile-based nanofiltration membrane prepared by the present invention has a separation skin layer prepared by complexation reaction of base membrane material, graphene oxide and polyelectrolyte, and is obtained by covalent crosslinking, and has good chemical stability. After the nanofiltration membrane was immersed in a hydrochloric acid solution with a pH of 2 and a sodium hydroxide solution with a pH of 13 at room temperature for 12 hours, the infrared spectrum of the membrane surface was measured, and it was found that the chemical structure of the membrane surface did not change significantly. At the same time, the separation performance of the hydrolyzed polyacrylonitrile-based nanofiltration membrane for Congo red was measured. The results showed that the flux of the membrane decreased after treatment with an acid solution, while the flux of the membrane increased after treatment with an alkaline solution, and the dye retention rate of the membrane increased. The above results show that the nanofiltration membrane has good chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 The present invention is a flow chart for preparing a hydrolyzed polyacrylonitrile-based nanofiltration membrane.

[0021] Figure 2 This is a scanning electron microscope photograph of the cross-sectional structure of the hydrolyzed polyacrylonitrile-based nanofiltration membrane prepared in the present invention.

[0022] Figure 3 This is a scanning electron microscope photograph of the cross-sectional structure of the hydrolyzed polyacrylonitrile-based nanofiltration membrane prepared in the present invention.

[0023] Figure 4 This is the separation performance diagram of hydrolyzed polyacrylonitrile-based nanofiltration membrane.

[0024] Figure 5 This is a performance test data chart of hydrolyzed polyacrylonitrile-based nanofiltration membrane.

[0025] Figure 6This is the infrared spectrum of the nanofiltration membrane surface after the nanofiltration membrane was immersed in hydrochloric acid solution (pH=2) and sodium hydroxide solution (pH=13) for 12 hours.

[0026] Figure 7 It is the separation performance of the nanofiltration membrane surface after the nanofiltration membrane is immersed in hydrochloric acid solution (pH=2) and sodium hydroxide solution (pH=13) for 12 hours. DETAILED DESCRIPTION

[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] H-PAN is used as the base film material, dissolved in a solvent, and GO is dispersed in the solvent by ultrasound, and the two are mixed in a certain proportion and mechanically stirred to obtain a uniform and transparent polymer solution, and the polymer solution is centrifuged and matured to obtain a casting solution. In this embodiment, the GO content is 0.005wt%, and the solid content of the polymer is 16wt%; the casting solution is poured onto a non-woven fabric at an ambient temperature of 30±5°C, and the film is scraped with a scraper with a knife gap of 150μm; after the solvent evaporates for 5s, the primary film is immediately placed in a 0.4wt% PEI solution and kept for 20min; the molecular weight of the above PEI is 10000Da, and the PEI solution is the coagulation bath; the membrane is taken out from the coagulation bath and placed in a 60°C 0.5% glutaraldehyde aqueous solution for 30min to fully react; the cross-linked nanofiltration membrane is taken out from the glutaraldehyde aqueous solution and placed in deionized water. Figure 2 (a) is a cross-sectional structural picture of the nanofiltration membrane prepared in this example. The cross section of the nanofiltration membrane consists of a dense skin layer, a porous transition layer and a support layer with deformed droplet-shaped macropores.

[0030] Testing of nanofiltration membrane performance: Cut the membrane into a circular shape and install it in an area with an effective test area of ​​3.14 cm 2 The test temperature is 25℃ and the operating test pressure is 0.4MPa. The membrane needs to be pre-pressed for 2h under the above pressure before the formal test. The main purpose is to examine the performance of pure water (dye solution) flux and dye retention rate.

[0031] Dye solution flux: The dye solution permeation flux (Flux, F) of the membrane can be measured by calculating the volume of water that passes through the effective area of ​​the nanofiltration membrane per unit time. Its unit is L·m -2 ·h -1 , the formula is as follows:

[0032]

[0033] Where V is the volume of water passing through the effective area of ​​the membrane per unit time, A is the effective area of ​​the membrane, and t is time.

[0034] Dye retention rate: Under the operating pressure of 0.4MPa, the concentration of Congo red is 50mg·L -1 When testing the dye retention of the nanofiltration membrane, the rejection rate (Rejection, R) is calculated by the following formula:

[0035]

[0036] Among them C p and C f They are the dye concentration in the permeate and the dye concentration in the mother liquor, respectively. Each set of separation performance data is based on the average data of three membrane samples tested simultaneously. The dye concentration is measured using a UV spectrophotometer. The dyes investigated are mainly Congo red (CR), Coomassie Brilliant Blue (BBR), Evans Blue (EB) and Direct Red 23 (DR23); if not specifically emphasized, the dye type used in this patent is Congo red (CR). Then, by collecting the dye solution that permeates the membrane and calculating the dye flux and retention rate of the membrane according to the formula, the test data results are shown in Figure 4 .

[0037] Example 2

[0038] The nanofiltration membrane was prepared according to the method of Example 1, except that the GO content in the casting solution was 0.01 wt%. The cross-sectional structure of the nanofiltration membrane is shown in FIG. Figure 2 (b) As shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0039] Example 3

[0040] The nanofiltration membrane was prepared according to the method of Example 1, except that the GO content in the casting solution was 0.02 wt %. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0041] Example 4

[0042] The nanofiltration membrane was prepared according to the method of Example 1, except that the GO content in the casting solution was 0.03 wt %. The cross-sectional structure of the nanofiltration membrane is shown in FIG. Figure 2 (c) The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0043] Example 5

[0044] The nanofiltration membrane was prepared according to the method of Example 1, except that the GO content in the casting solution was 0.04 wt %. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0045] Example 6

[0046] The nanofiltration membrane was prepared according to the method of Example 1, except that the GO content in the casting solution was 0.05 wt %. The cross-sectional structure of the nanofiltration membrane is shown in FIG. Figure 2 (d) As shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0047] Example 7

[0048] The nanofiltration membrane was prepared according to the method of Example 1, except that the GO content in the casting solution was 0.01wt%, and the PEI concentration in the coagulation bath was 0.2wt%. The cross-sectional structure of the nanofiltration membrane is shown in FIG. Figure 2 (e) As shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0049] Example 8

[0050] The nanofiltration membrane was prepared according to the method of Example 1, except that the GO content in the casting solution was 0.01wt%, and the PEI concentration in the coagulation bath was 0.6wt%. The cross-sectional structure of the nanofiltration membrane is shown in FIG. Figure 2 (f) As shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0051] Example 9

[0052] The nanofiltration membrane was prepared according to the method of Example 1, except that the GO content in the casting solution was 0.01wt%, and the PEI concentration in the coagulation bath was 0.8wt%. The pure water flux, dye solution permeation flux, and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0053] Example 10

[0054] H-PAN is used as the base membrane material, which is dissolved in a solvent, and after centrifugation and maturation, a casting solution with a solid content of 16wt% is obtained. A GO dispersion with a concentration of 0.01wt% is mixed with a series of polyelectrolyte solutions of different concentrations to obtain a clear and transparent graphene oxide-polyelectrolyte mixed solution, and the mixed solution is used as a coagulation bath to form a membrane. In this embodiment, the molecular weight of PEI in the coagulation bath is 10000Da, and the mass ratio of PEI to GO is 40:1. The above-mentioned casting solution is poured onto a non-woven fabric at an ambient temperature of 30±5°C, and the film is scraped with a scraper with a blade gap of 150μm; after scraping, the primary membrane is immediately immersed in a coagulation bath for phase inversion and maintained for 20 minutes. The membrane is taken out of the coagulation bath and placed in a 60°C 0.5% glutaraldehyde aqueous solution for 30 minutes for sufficient reaction; the cross-linked nanofiltration membrane is taken out of the glutaraldehyde aqueous solution and placed in deionized water for standby use. The cross-sectional structure picture of the nanofiltration membrane is shown in Figure 3 (a) is shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0055] Embodiment 11

[0056] The nanofiltration membrane was prepared according to the method of Example 10, except that the mass ratio of PEI to GO in the coagulation bath was 80:1. Figure 3 (b) As shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0057] Example 12

[0058] The nanofiltration membrane was prepared according to the method of Example 10, except that the mass ratio of PEI to GO in the coagulation bath was 120:1. Figure 3 (c) The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0059] Embodiment 13

[0060] The nanofiltration membrane was prepared according to the method of Example 10, except that the mass ratio of PEI to GO in the coagulation bath was 160:1. Figure 3 (d) As shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0061] Embodiment 14

[0062] The nanofiltration membrane was prepared according to the method of Example 10, except that the mass ratio of PEI to GO in the coagulation bath was 200:1. Figure 3 (e) As shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0063] Embodiment 15

[0064] The nanofiltration membrane was prepared according to the method of Example 10, except that the mass ratio of PEI to GO in the coagulation bath was 240:1. Figure 3 (f) As shown. The pure water flux, dye solution permeation flux and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0065] Example 16

[0066] The nanofiltration membrane was prepared according to the method of Example 10, except that the molecular weight of PEI in the coagulation bath was 600 Da, and the mass ratio of PEI to GO was 160:1. The pure water flux, dye solution permeation flux, and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0067] Embodiment 17

[0068] The nanofiltration membrane was prepared according to the method of Example 10, except that the molecular weight of PEI in the coagulation bath was 70000Da, and the mass ratio of PEI to GO was 160:1. The pure water flux, dye solution permeation flux, and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0069] Embodiment 18

[0070] The nanofiltration membrane was prepared according to the method of Example 10, except that the polyelectrolyte in the coagulation bath was polyallylamine (PAM), wherein the mass ratio of PAM to GO was 40:1. The pure water flux, dye solution permeation flux, and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0071] Comparative Example 1

[0072] H-PAN was used as the base membrane material to prepare a casting solution with a solid content of 16 wt%. Deionized water was used as the coagulation bath to prepare the nanofiltration membrane. The pure water flux, dye solution permeation flux, and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0073] Comparative Example 2

[0074] H-PAN was used as the base membrane material to prepare a casting solution with a solid content of 16 wt%. A nanofiltration membrane was prepared using a 0.005 wt% GO dispersion as a coagulation bath. The pure water flux, dye solution permeation flux, and dye retention rate of the nanofiltration membrane were measured. The results are shown in Figure 4 .

[0075] Comparative Example 3

[0076] Using H-PAN as the base film material,

[0077] Prepare a casting solution with a solid content of 16wt%. Prepare a nanofiltration membrane using a 0.4wt% PEI solution as a coagulation bath. Determine the pure water flux, dye solution permeation flux, and dye retention rate of the nanofiltration membrane. The results are shown in Figure 4 .

[0078] exist Figure 4 The separation performances of the samples prepared in Comparative Example 1 and Examples 1-6 are shown in the figure; Figure 5 In: S1 to S18 represent Examples 1 to 18, and D1 to D3 represent Comparative Examples 1 to 3.

[0079] As can be seen from Comparative Example 1, a nanofiltration membrane was prepared using H-PAN as the base membrane material and deionized water as the coagulation bath. The dye retention rate of the membrane is low, only 80.5%. As can be seen from Comparative Example 2, the nanofiltration membrane prepared using H-PAN as the base membrane material and GO dispersion as the coagulation bath also has a low dye retention rate of only 82.1%. As can be seen from Comparative Example 3, the nanofiltration membrane prepared using H-PAN as the base membrane material and PEI aqueous solution as the coagulation bath has a dye retention rate of 97.7%. This shows that adding PEI to the coagulation bath can increase the retention rate of the membrane.

[0080] Comparison between Comparative Example 2 and Example 12 shows that when GO and PEI are present in the coagulation bath, the dye retention rate of the membrane is 99.8%, which is 17.7% higher than that of Comparative Example 2. Comparison between Comparative Example 3 and Example 12 shows that when GO and PEI are present in the coagulation bath, the flux of the membrane is 904.4 L·m -2 ·h -1 , which is 1.69 times that of the nanofiltration membrane prepared in comparative example 2. Comparison between comparative example 3 and example 5 shows that the dye retention rate of the nanofiltration membrane prepared by adding GO to the casting solution and using PEI aqueous solution as the coagulation bath is 99.3%, which is 1.6% higher than that of comparative example 3; the flux is 1136.9 L·m -2 ·h -1 , which is 2.12 times that of the nanofiltration membrane prepared in comparative example three.

[0081] The nanofiltration membrane prepared in Example 2 was immersed in a hydrochloric acid solution with a pH of 2 and a sodium hydroxide solution with a pH of 13 at room temperature for 12 hours, and the infrared spectrum and separation performance of the membrane surface were measured. Figure 6 and 7 As shown. Figure 6 (a) Compared with the untreated membrane, Figure 6The infrared spectra of the membrane surface treated with (b) hydrochloric acid solution and (c) sodium hydroxide solution are basically the same, indicating that the chemical structure of the membrane surface has not changed significantly after being soaked in acid and alkali solutions. However, the flux of the membrane increased after being treated with alkali solution, and the dye retention rate of the membrane increased. The above results show that the nanofiltration membrane has good chemical stability.

[0082] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hydrolyzed polyacrylonitrile-based nanofiltration membrane, characterized in that: The following steps are involved: (1) dissolving hydrolyzed polyacrylonitrile in an organic solvent to prepare a casting solution; (2) dissolving the polyelectrolyte in water to prepare a coagulation bath; (3) After the casting liquid is formed into a membrane, it is immersed in a coagulation bath for solidification to obtain a hydrolyzed polyacrylonitrile-based nanofiltration membrane; Graphene oxide is added to the casting solution, and the concentration of graphene oxide is 0.005-0.05 wt %; or graphene oxide is added to the coagulation bath, and the mass ratio of polyelectrolyte to graphene oxide is 40-240:1; The polyelectrolyte is polyethyleneimine or polyallylamine; The hydrolyzed polyacrylonitrile-based nanofiltration membrane prepared in step (3) is cross-linked with glutaraldehyde, wherein the solidified hydrolyzed polyacrylonitrile-based nanofiltration membrane is placed in a glutaraldehyde aqueous solution with a concentration of 0.1-1wt% and reacted for 20-60 minutes.

2. The method for preparing a hydrolyzed polyacrylonitrile-based nanofiltration membrane according to claim 1, characterized in that: The organic solvent is N,N-dimethylformamide or N,N-dimethylacetamide.

3. The method for preparing a hydrolyzed polyacrylonitrile-based nanofiltration membrane according to claim 2, characterized in that: The concentration of hydrolyzed polyacrylonitrile in the casting solution is 15-17 wt %.

4. The method for preparing a hydrolyzed polyacrylonitrile-based nanofiltration membrane according to claim 3, characterized in that: The concentration of the polyelectrolyte in the coagulation bath is 0.1-1 wt %.

5. A hydrolyzed polyacrylonitrile-based nanofiltration membrane prepared according to the method according to any one of claims 1 to 4.

6. Use of the hydrolyzed polyacrylonitrile-based nanofiltration membrane according to claim 5 in wastewater treatment.

Citation Information

Patent Citations

  • Method for preparing nanofiltration membrane by adopting layer-by-layer self-assembly method

    CN105169962A